Integration of mass spectral fingerprinting analysis with precursor ion (MS1) quantification for the characterisation of botanical extracts: application to extracts of Centella asiatica (L.) Urban - Alcazar Magana, Armando (Phytochem Anal, 2020)
INTRODUCTION: The phytochemical composition of plant material governs the bioactivity and potential health benefits as well as the outcomes and reproducibility of laboratory studies and clinical trials. OBJECTIVE: The objective of this work was to develop an efficient method for the in‐depth characterisation of plant extracts and quantification of marker compounds that can be potentially used for subsequent product integrity studies. Centella asiatica (L.) Urb., an Ayurvedic herb with potential applications in enhancing mental health and cognitive function, was used as a case study. METHODS: A quadrupole time‐of‐flight analyser in conjunction with an optimised high‐performance liquid chromatography (HPLC) separation was used for in‐depth untargeted fingerprinting and post‐acquisition precursor ion quantification to determine levels of distinct phytochemicals in various C. asiatica extracts. RESULTS: We demonstrate the utility of this workflow for the characterisation of extracts of C. asiatica. This integrated workflow allowed the identification or tentative identification of 117 compounds, chemically interconnected based on Tanimoto chemical similarity, and the accurate quantification of 24 phytochemicals commonly found in C. asiatica extracts. CONCLUSION: We report a phytochemical analysis method combining liquid chromatography, high resolution mass spectral data acquisition, and post‐acquisition interrogation that allows chemical fingerprints of botanicals to be obtained in conjunction with accurate quantification of distinct phytochemicals. The variability in the composition of specialised metabolites across different C. asiatica accessions was substantial, demonstrating that detailed characterisation of plant extracts is a prerequisite for reproducible use in laboratory studies, clinical trials and safe consumption. The methodological approach is generally applicable to other botanical products.